Manto's legendary contribution to partition literature of India - Akram, Lubna; Hanifa, Mohamed Ali; Rathakrishnan, Mohan (Univerisiti Malaya, 2019)
This article discusses the consequences of the partition of India that was explored from the perspective of Manto’s writing on the major aspects of the partition. The major theme of this specific area of literature is the communal violence and its effects. This violence included rape, murder, abduction of women, violation of holy places, loss of life, kidnapping and the distorted identity of a generation. Statistical data and history does not portray the emotions and sufferings of the people. Writers of that time including Manto did a tremendous job in portraying the true picture of the situation. Manto, a legendary writer, has a collection of short stories based on the real sufferings of the people whether they are common people or people of high status. His major themes are killing, kidnapping, rape, revenge and looting, revolving around victimized women and their issues.